Transit Time Measurement in Indicator Dilution Curves: Overcoming the Missing Ground Truth and Quantifying the Error - Naber, Ady; Reiß, Michael; Nahm, Werner (Frontiers in Physiology, 2021)
3 The vascular function of a vessel can be qualitatively and intraoperatively checked by recording 4 the blood dynamics inside the vessel via fluorescence angiography (FA). Although FA is the 5 state of the art in proving the existence of blood flow during interventions such as bypass 6 surgery, it still lacks a quantitative blood flow measurement which could decrease the recurrence 7 rate and postsurgical mortality. Previous approaches show that the measured flow has a 8 significant deviation compared to the gold standard reference (ultrasonic flow meter). In order 9 to systematically address the possible sources of error, we investigated the error in transit time 10 measurement of an indicator. Obtaining in vivo indicator dilution curves with a known ground 11 truth is complex and often not possible. Further, the error in transit time measurement should 12 be quantified and reduced. To tackle both issues, we first computed many diverse indicator 13 dilution curves using an in silico simulation of the indicator’s flow. Second, we post-processed 14 these curves to mimic measured signals. Finally, we fitted mathematical models (parabola, 15 gamma variate, local density random walk and mono-exponential model) to re-continualize 16 the obtained discrete indicator dilution curves and calculate the time delay of two analytical 17 function. This re-continualization showed an increase of the temporal accuracy up to a sub- 18 sample accuracy. Thereby, the Local Density Random Walk (LDRW) model performed best using 19 the cross-correlation of the first derivative of both indicator curves with a cutting of the data at 20 40% of the peak intensity. The error depends on the noise level and is for a signal-to-noise ratio 21 (SNR) of 20 dB and a sampling rate of f = 60 H z at f −1 · 0.25(±0.18), so this error is smaller ss 22 than the distance between two consecutive samples. The accurate determination of the transit 23 time and the quantification of the error allow the calculation of the error propagation onto the flow measurement. Both can assist surgeons as an intraoperative quality check and thereby reduce the recurrence rate and post-surgical mortality.